The Fleas (Siphonaptera) in Iran: Diversity, Host Range, and Medical Importance. - Naseh Maleki-Ravasan; Samaneh Solhjouy-Fard; Jean-Claude Beaucournu; Anne Laudisoit; Ehsan Mostafavi (Public Library of Science (PLoS), 2017)
BACKGROUND:Flea-borne diseases have a wide distribution in the world. Studies on the identity, abundance, distribution and seasonality of the potential vectors of pathogenic agents (e.g. Yersinia pestis, Francisella tularensis, and Rickettsia felis) are necessary tools for controlling and preventing such diseases outbreaks. The improvements of diagnostic tools are partly responsible for an easier detection of otherwise unnoticed agents in the ectoparasitic fauna and as such a good taxonomical knowledge of the potential vectors is crucial. The aims of this study were to make an exhaustive inventory of the literature on the fleas (Siphonaptera) and range of associated hosts in Iran, present their known distribution, and discuss their medical importance. METHODOLOGY/PRINCIPAL FINDINGS:The data were obtained by an extensive literature review related to medically significant fleas in Iran published before 31st August 2016. The flea-host specificity was then determined using a family and subfamily-oriented criteria to further realize and quantify the shared and exclusive vertebrate hosts of fleas among Iran fleas. The locations sampled and reported in the literature were primarily from human habitation, livestock farms, poultry, and rodents' burrows of the 31 provinces of the country. The flea fauna were dominated by seven families, namely the Ceratophyllidae, Leptopsyllidae, Pulicidae, Ctenophthalmidae, Coptopsyllidae, Ischnopsyllidae and Vermipsyllidae. The hosts associated with Iran fleas ranged from the small and large mammals to the birds. Pulicidae were associated with 73% (56/77) of identified host species. Flea-host association analysis indicates that rodents are the common hosts of 5 flea families but some sampling bias results in the reduced number of bird host sampled. Analyses of flea-host relationships at the subfamily level showed that most vertebrates hosted fleas belgonging to 3 subfamilies namely Xenopsyllinae (n = 43), Ctenophthalminae (n = 20) and Amphipsyllinae (n = 17). Meriones persicus was infested by 11 flea subfamilies in the arid, rocky, mountainous regions and Xenopsyllinae were hosted by at least 43 mammal species. These findings place the Persian jird (M. persicus) and the Xenopsyllinae as the major vertebrate and vector hosts of flea-borne diseases in Iran including Yersinia pestis, the etiological agent of plague. We found records of at least seven vector-borne pathogenic agents that can potentially be transmitted by the 117 flea species (or subspecies) of Iran. CONCLUSIONS/SIGNIFICANCE:Herein, we performed a thorough inventary of the flea species and their associated hosts, their medical importance and geographic distribution throughout Iran. This exercise allowed assessing the diversity of flea species with the potential flea-borne agents transmission risk in the country by arranging published data on flea-host associations. This information is a first step for issuing public health policies and rodent-flea control campaigns in Iran as well as those interested in the ecology/epidemiology of flea-borne disease.